Highly dispersed cobalt decorated uniform nitrogen doped graphene derived from polydopamine positioning metal-organic frameworks for highly efficient electrochemical water oxidation. (1st November 2018) - Zhao, Qiuyue; Zhang, Qi; Fu, Mingxuan; Liu, Yuexian; Sun, Yuena; Lu, Haijun; Fan, Xinyu; Zhang, Yufan; Wang, Huan
Abstract: The development of high-performance noble metal-free electrochemical catalyst for effective water splitting is a key factor to achieve low-cost and sustainable renewable energy production. Herein, for the first time, highly dispersed cobalt nanoparticles decorated uniform nitrogen doped graphene (CoNPs-N-GR) was design synthesized. In the preparation procedure, graphene oxide (GO) was employed as supporting material, polydopamine as nitrogen source, location reagent as well as connecting agent for uploading cobalt metal ion, and then cobalt metal-organic frameworks (ZIF-67) in situ grew on GO. During the calcining process, GO reduction, nitrogen doping and cobalt nanoparticles forming were finished in one step. Scanning electron microscopy (SEM) images, transmission electron microscopy (TEM), energy-dispersive X-ray (EDS), X-ray photoelectron spectrometer (XPS) and X-ray diffraction (XRD) were applied to characterize the as-prepared CoNPs-N-GR. Moreover, owing to the presence of dopamine, high dispersed cobalt nanoparticles were obtained, leading to high electrocatalytic activity of CoNPs-N-GR for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline media. HER reaches 10 mA cm −2 at the over-potential of 0.453 V with a Tafel slope of 67 mV dec −1 . OER reaches 10 mA cm −2 at the over-potential of 1.63 V with a Tafel slope of 65 mV dec −1 . And the as-prepared CoNPs-N-GR shows excellent durability in the long-term stability for HER and OER. Graphical abstract: Highlights: Highly dispersed CoNPs decorated uniform nitrogen doped graphene was prepared. Polydopamine as nitrogen source, location reagent as well as connecting agent. In situ grow of cobalt metal-organic frameworks (ZIF-67) as cobalt precursor. High electrocatalytic performance for both HER and OER in alkaline media.